STANDARISASI KOREKSI DATA SATELIT MULTIWAKTU DAN MULTISENSOR (LANDSAT TM/ETM+ DAN SPOT-4) - Trisakti, Bambang; Nugroho, Gagat (Institut Teknologi Sepuluh Nopember, 2012)
Remote sensing satellite data has been widely used to support watershed and lake managements. However researches conducted in Indonesia are facing common problems related with standardization of data pre-processing, particularly that are related to orthorectification and radiometric correction. The objective of this research is to standardize the satellite data correction to monitor Total Suspended Material (TSM) in Limboto lake along 1990-2010 period using Landsat TM/ETM+ and SPOT-4. The data correction process was performed included orthorectification, sun correction, terrain correction and normalization of data with different time and different sensor. The result of each correction process was examined to evaluate the quality improvement before and after correction. The corrected data was then used to monitor the degree of turbidity of Limboto Lake during 1990-2010 periods. The study results show that data correction reduces position error and object spectral difference due to differences in acquisition time and sensor. The examined correction provides more accurate and consistent results. The quality of Limboto Lake was monitored decreases gradually, where the higher TSM concentration was found during the period of 1990-2010.